Twelve weeks of progressive resistance training positively improves physical fitness and golf swing performance in talented youth golfers - Shaw, J.; Gould, Z. I.; Oliver, J. L.; Lloyd, R. S. (The Journal of Strength and Conditioning Research, 2024)
This aim of this study was to investigate the effects of a 12-week resistance training program in talented junior golfers. Eighteen talented youth golfers were pair matched by maturity status and handicap, and subsequently allocated to an experimental (EXP) or control group. During the 12-week intervention, both groups continued with their normal golf practice while the EXP group also completed a progressive twice-weekly resistance training program. At baseline, subjects performed multiple trials of an isometric midthigh pull (IMTP), countermovement jump (CMJ), standing long jump, golf movement screen (GMS), and isometric plank hold. Club head speed (CHS) and carry distance for a 6-iron and driver were also measured using a commercial launch monitor. When controlled for maturity offset, there were significant (p < 0.05) interaction effects in favor of the EXP group for absolute (g = 1.29) and relative (g = 2.06) peak force for the IMTP, CMJ absolute (g = 0.73) and relative (g = 0.66) peak power, jump height (g = 1.05), modified reactive strength index (g = 1.30), lateral (g = 0.48-0.88) and horizontal jump distance (g = 1.20), and GMS total score (g = 1.07). Significant interaction effects were also reported in 6-iron and driver CHS and carry distance in favor of the EXP group (p < 0.05; g = 0.41-1.64). These findings indicate that twice-weekly resistance training in combination with regular golf practice can stimulate increases in measures of strength, power, and movement competency in youth golfers, which should contribute to enhanced golf swing performance.